The Effect of Intensive Reading Strategy on Students’ Reading Comprehension - Meikardo Samuel Prayuda (JOLADU: Journal of Language Education, 2023)
This research was purposed to find out whether intensive reading strategy could give significance effect to the students’ reading comprehension. The location of this research was at SMA Negeri 1 Sei.Balai. The time that was alocated in this research was one month. This study was conducted in Experimental study. The method in taking the sample was random sampling. The population of this research was all of grade XI students that consisted of four classes. There were  IPA1 that consisted of 35 students, X IPA2 that consisted of 35 students, and X IPS1 that consisted of 35 students. Because of this study used experimental, the researcher chose X IPA2 as experiment class and X IPS1 as control class based on the random sampling. The instruments that used in this study was test. The test was divided into two, there were pre-test and post test. Both tests consisted of 10 items. In this study, the the study applied the pre-test in both control and experiment groups. After that, the study applied the teaching process by using intensive reading strategy in experiment class and conventional way in control class. From the data, it could be concluded that teaching reading by using intensive reading strategy could give significance effect to the students’ reading comprehension. For that conclusion, the hypotheses Ha which is There is an effect of intensive reading on students’ reading comprehension at grade X IPA2 students of SMA Negeri 1 Sei.Balai in academic year of 2022/2023”, was accepted.